1974
DOI: 10.1113/jphysiol.1974.sp010642
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of crayfish neuromuscular facilitation and their calcium dependence

Abstract: SUMMARY1. A quantitative description of facilitation in the crayfish claw opener muscle is presented. The facilitation of a test response following one or more conditioning stimuli, and the growth of facilitation during a tetanus, are measured.2. In superficial central fibres facilitation following one or more impulses can be described as the sum of two components which are both maximum at the end of the conditioning train and decline simultaneously and exponentially with different time constants thereafter.3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
2

Year Published

1974
1974
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 37 publications
5
57
2
Order By: Relevance
“…However, e.j.p.s could still be recorded in deep fibres, and very slight movement occurred at very high frequencies (over 30 Hz). Apparently, y-MG fails to penetrate below the muscle surface fibres (see Zucker, 1974a).…”
Section: Resultsmentioning
confidence: 99%
“…However, e.j.p.s could still be recorded in deep fibres, and very slight movement occurred at very high frequencies (over 30 Hz). Apparently, y-MG fails to penetrate below the muscle surface fibres (see Zucker, 1974a).…”
Section: Resultsmentioning
confidence: 99%
“…Reduced [Ca2+]e, at a level of 0.1mM free-Ca2+ (buffered in Mg2 +-EDTA; Zucker, 1974) was tested in five preparations; in four of these, more impulses were required to produce blockage and in one there was no significant difference. Elevated [Ca2 +]e appeared to have the opposite effect.…”
Section: Effects Of Changing the Bath Composition And Temperaturementioning
confidence: 99%
“…In the classic "residual calcium model" (Katz and Miledi, 1968) a highly nonlinear relationship between [Ca2+] and release is used to account for the observation that increased residual calcium produces a large enhancement of action potential-evoked release without causing a continuously high rate of spontaneous release. This model, while qualitatively able to account for the rapid decay of short-term facilitation, is unable to account quantitatively for many properties of the buildup and decay of synaptic enhancement (e.g., Zucker, 1974b;Zucker and Fogelson, 1986;Magleby, 1987). More recent modifications of the residual Ca*+ model for the shortestlasting phases of facilitation (persisting for = 1 set or less) have suggested that the decay of this process is set by the reverse rate of a Ca2+-activated process such as the dissociation rate of Ca2+ from a facilitating site, rather than the decay of free Ca*+ in the cytoplasm (Balnave and Gage, 1974;Stanley, 1986;Robitaille and Charlton, 199 1;Yamada and Zucker, 1992).…”
mentioning
confidence: 99%